The change in roles of architec's and quantity surveyor's from conventional to partnering approach - Suratkon, Azeanita (2004)
Architects and quantity surveyors are among the principal stakeholder using partnering. Partnering is intended to improve the way projects are designed and constructed. Consequently, partnering has a n impact on the d esign and construction process. This research project aims to investigate how the various aspects of an architect's and quantity surveyor's job have changed when comparing conventional projects with those involving a partnering agreement. This study intends to identify the practical impact of partnering on the architect's and quantity surveyor's role in the construction process and ascertain the strategy undertaken by the architect and quantity surveyor to adapt to partnering. The means of data collection used was a postal questionnaire distributed to architects and quantity surveyors with partnering experience. Two separate sets of questionnaires were produced for each category of respondent and were designed to allow comparisons to be drawn between the architect and quantity surveyor. Based on the literature review, partnering benefits and impacts were grouped into seven headings. The results obtained, do not support the hypotheses that partnering has a great impact on their roles and practices. They perceived that the highest severities of impacts are at major scale: procurement and contract issue for the architects, information exchange and dispute avoidance and resolution issues for the quantity surveyor. The survey revealed that an architect's role as a designer is the most frequently adopted in a partnering approach compared to lead consultant and contract administrator in a conventional approach, whereas, a quantity s urveyor's r ole as a cost adviser remains dominant. These do not support the hypotheses that their roles adopted in a conventional approach will change radically in a partnering approach. The hypotheses that a quantity surveyor is more flexible than an architect in adapting to change imposed by a partnering approach are also not supported by the results. The results do suggest that an architect has a preference to develop a close relationship with design-build contractors, while quantity surveyors prefer to market themselves to clients who can potentially initiate partnering arrangements as a strategy to adapt in a competitive partnering market. The role as an independent client adviser and project manager are the two roles discovered by the survey as potentially the most suitable potential to architects and quantity surveyors to take on as alternative roles in a partnering era.